Nonstoichiometry and hole doping in NiO (2010)
ABSTRACT: We have study by means of DFT+U and thermodynamic calculations the doping response of the p-type transparent oxide NiO. We have found from the calculated defect formation enthalpies that Ni vacancy, not the O interstitial, is the main source of nonstoichiometry in NiO. On the other hand, the calculated free-hole concentration at room temperature of pure NiO remains very low compared to the concentration of Ni vacancies; this is due to the too large ionization energy of the Ni vacancy. The free-hole concentration can be strongly increased by extrinsic dopants with a more shallow donor as it is illustrated for the case of Li.